The development and validation of the assessment engagement scale - Evans, Carol; Zhu, Xiaotong (Frontiers in Psychology, 2023)
Introduction The quality of student engagement in assessment within higher education affects learning outcomes. However, variations in conceptions of what quality in engagement looks like impacts assessment design and the way that students and lecturers engage with each other in the assessment process. Given that assessment is an important driver of student engagement in higher education, it is surprising that no specific measures to support understanding of this measure exist. To address this significant gap, we outline the evolution of an assessment engagement scale derived from a research-informed conceptual framework utilizing best practice in assessment and feedback. Methods We consider the validity and utility of the assessment engagement scale in supporting students’ understanding of assessment and their role within it using exploratory and confirmatory factor analyses. Results The resultant nine-item assessment engagement scale’s underpinning two factors included: (i) Understanding of the Assessment Context (UAC) including one’s role within it, and confidence in navigating assessment requirement, and (ii) Realising Engagement Opportunities (REO) (i.e., willingness to engage and ability to utilise the assessment context effectively to support one’s understanding). Construct, criterion, and convergent validity of the scale were established. Discussion The AES is a powerful tool in promoting dialogue between lecturers and students about what high quality engagement in assessment looks like, and the respective roles of all parties in realising this. Implications for assessment practices are discussed along with the potential of the scale as a predictive and developmental tool to support enhancements in assessment design and student learning outcomes in higher education.